Säkerhetszoner – Brottsförebyggande framsteg eller rättsstatligt bakslag? - Neculcea,Isabell (2025)
This thesis explores the legal implications of introducing so-called security zones in Sweden and analyzes them from a rule of law perspective. These zones allow police to conduct body searches and vehicle inspections without requiring specific criminal suspicion within designated geographic areas. Introduced as part of the Tidö Agreement (Tidöavtalet) and now legislated, security zones aim to combat escalating violence, particularly shootings and bombings linked to organized crime. This legislative shift has sparked extensive debate, as it challenges fundamental principles of the rule of law, individual privacy, and protection against arbitrary interference. The research question is of significant interest as the legal framework surrounding security zones reflects a shift towards prioritizing crime prevention at the potential expense of procedural safeguards. The primary objective of this thesis is to critically evaluate the arguments in favor of this legal reform and assess its compatibility with the Swedish Constitution, the European Convention on Human Rights, and key legal principles, including the principles of protection and presumption of innocence. The study primarily uses a legal dogmatic methodology, which involves systematic interpretation of current law through legislative texts, preparatory works, case law, and legal literature. It also includes a comparative element, examining how similar frameworks have functioned in countries like Denmark and the United Kingdom. The findings reveal that while security zones may enhance law enforcement efficiency, they also pose a significant risk to legal certainty, increase the likelihood of discriminatory practices, and may lead to ethnic profiling. Jurisprudence from the European Court of Human Rights emphasizes the importance of clear legal criteria and procedural safeguards to ensure compliance with the right to privacy and protection from body searches. In conclusion, the current implementation of security zones may undermine public trust in the legal system, particularly among vulnerable populations. To ensure that such measures meet essential legal standards, the thesis advocates for stricter proportionality assessments, greater transparency in decision-making, and accessible judicial oversight. This study underscores the necessity for a cautious and legally sound approach to security policy that does not compromise the fundamental values of democratic rule of law. Security zones are therefore not considered to be following the legal safeguards offered by procedural protection, particularly regarding the principle of protection and the presumption of innocence.
Keywords: straffrätt; criminal law; säkerhetszoner; kroppsvisitation; rättssäkerhet; förverkligandeprincipen; skyddsprincipen; polisiära befogenheter; tvångsmedel; polislagen; Tidöavtalet; brottsförebyggande arbete; security zones; stop and search; rule of law; proactive policing; criminal justice priniples; presumption of innocence; oskyldighetspresumtionen; skuldpresumtionen; procedural safeguards:crime prevention policy; the presumption of guilt